2020
DOI: 10.29252/iem.6.4.269
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Multidrug-Resistant, Extensively Drug-Resistant, and Pandrug-Resistant Phenotypes among Clinical Isolates of Staphylococcus aureus

Abstract: How to cite this article Sadat S.S., Ahani Azari A. Frequency of Multidrug-Resistant, Extensively Drug-Resistant, and Pandrug-Resistant Phenotypes among Clinical Isolates of Staphylococcus aureus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In the present study, more than half of S. aureus isolates from impetigo, and 40.8% of those from all skin infections were MRSA. These findings are in line with the findings of a previous study in Iran (13). Similarly, two other studies in Iran reported that more than half of all isolates from skin infections were MRSA (14,15).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, more than half of S. aureus isolates from impetigo, and 40.8% of those from all skin infections were MRSA. These findings are in line with the findings of a previous study in Iran (13). Similarly, two other studies in Iran reported that more than half of all isolates from skin infections were MRSA (14,15).…”
Section: Discussionsupporting
confidence: 92%
“…Different concentrations of the extract (25, 12.5, 6.25, 3.12 mg/mL) were prepared by serial dilution method [10] . Microorganisms: The antibacterial effect of each extract at different concentrations was assessed against MRSA (n=24) and MDR P. aeruginosa (n=16) isolates from our previous study [11][12] . In previous study, methicillin resistance was evaluated using 30 μg cefoxitin disk (≤21 mm indicated MRSA) and 1 μg oxacillin disk (≤10 mm indicated MRSA) [13] .…”
Section: Plant Materials and Preparation Of Extractsmentioning
confidence: 99%
“…A review of the bioactivity and potential ... [9] Izadi Z, Modarres Sanavi SAM, Sorooshzadeh A, Esna-Ashari M, Davoodi P. Antimicrobial activity of chamomile (Matricaria chamomilla L.) and feverfew (Tanacetum parthenium L.). Armaghane-Danesh J Yasuj .... [10] Imeni N, Qayami Rad M. In vitro antibacterial effect of ethanolic extract of Calendual officinalis L. against Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, and Pseudomonas ... [11] Poudineh F, Ahani Azari A, Fozouni L. Incidence of multidrug-resistant, extensively ... [12] Sadat SS, Ahani Azari A. Frequency of multidrugresistant, extensively ...…”
mentioning
confidence: 99%